Estudo de bioequivalência de duas formulações de atenololem voluntários sadios de ambos os sexos e genotipagem dospolimorfismos dos genes eca e cyp2d6*4 - Irilda de Oliveira Costa (2010)
There were several factors involved in the adoption of drug policies that could culminate with the populations access to them. Thus, with the application of law n° 9.787 from February 10, 1999, began the bioequivalence studies, which basically refer to the comparison of the main pharmacokinetic measures observed in the experiment, for products to be tested. Moreover, the pharmacogenetics studies the genetic differences of the individuals in drug biotransformation. The genetic polymorphism contribute to the formation of different genotypic patterns that form the basis for individual variations and susceptibility to drugs. In that context, it was validated the bioanalytical method by high performance liquid chromatography coupled mass spectrometry (LCMS/MS) with liquid-liquid extraction for atenolol and was performed thegenotyping of polymorphs from angiotensin converting enzyme (ACE) andmetabolizer with reduced enzyme activity of CYP2D6 (CYP2D6*4) genes, in volunteers participating in the bioequivalence study and their respectivegenotypic and allelic frequencies were determined. The validated bioanalytical method according to FDA standards and ANVISA proved to be adequate the assessment of atenolol formulations (test and reference), when the drugs are bioequivalent. On the results obtained for the polymorphisms it can be concluded that there is a difference between the test and reference drug, but it did not affect the outcome of the bioequivalence between the two formulations. Key words: Atenolol, bioequivalence, LC-MS/MS, CYP2D6*4, ACE, polymorphism.